2011
DOI: 10.1111/j.2040-1124.2011.00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of wild‐type and mutant S20G hIAPP in physiologic knock‐in mouse models fails to induce islet amyloid formation, but induces mild glucose intolerance

Abstract: Aims/Introduction:  Human islet polypeptide S20G mutation (hIAPPS20G) is associated with earlier onset type 2 diabetes and increased amyloidogenicity and cytotoxicity in vitro vs wild‐type hIAPP (hIAPPWT), suggesting that amyloidogenesis may be pathogenic for type 2 diabetes. We compared the contributions of hIAPPS20G and hIAPPWT toward intra islet amyloid formation and development of type 2 diabetes in a unique physiologic knock‐in mouse model.Materials and Methods:  We replaced the mouse IAPP gene (M allele)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…The results showed lack of amyloid deposits even in 34-week-old high-fat diet-fed hIAPP:Atg7 fl/fl :Cre mice. To date, various transgenic rodent models for hIAPP have been reported; some showed amyloid deposits while others did not, depending on the experimental context, presumably due to the difference in gene expression dose of hIAPP, diet condition, and/or genetic background of models examined (13,17). Recent studies proposed that insoluble hIAPP amyloid fibrils are not toxic in β cells, but soluble toxic oligomers for hIAPP are responsible for hIAPP-induced cytotoxicity, which is collectively known as toxic oligomer hypothesis (51).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed lack of amyloid deposits even in 34-week-old high-fat diet-fed hIAPP:Atg7 fl/fl :Cre mice. To date, various transgenic rodent models for hIAPP have been reported; some showed amyloid deposits while others did not, depending on the experimental context, presumably due to the difference in gene expression dose of hIAPP, diet condition, and/or genetic background of models examined (13,17). Recent studies proposed that insoluble hIAPP amyloid fibrils are not toxic in β cells, but soluble toxic oligomers for hIAPP are responsible for hIAPP-induced cytotoxicity, which is collectively known as toxic oligomer hypothesis (51).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in these models have shown that overexpression of hIAPP exhibits toxic effects on β cells by inducing apoptosis and amyloidogenesis in a context-dependent manner. However, these traditional transgenic approaches resulted in large phenotypic variations, presumably due to multiple copy insertions that affect the expression levels and integration of genes near other transcriptional control elements that can adversely modulate expression (17). Expression of hIAPP driven by rat insulin promoter (RIP) is expected to be largely different from that regulated by the endogenous murine Iapp gene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C57BL/6NHsd mice (Harlan, Indianapolis, IN, USA) with wild-type h IAPP or S20G h IAPP knocked into the endogenous mouse Iapp locus [8] were bred and maintained at the VA Puget Sound Health Care System (VAPSHCS). Islets from 10-week-old male or female mice were isolated by collagenase digestion, recovered overnight in RPMI 1640 medium and subsequently cultured in media containing either 11.1 or 16.7 mmol/l glucose for 144 h, with media being renewed every 48 h. The VAPSHCS Institutional Animal Care and Use Committee approved the studies.…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, we used transgenic islets from mice in which wild-type h IAPP or S20G h IAPP had been knocked into the endogenous mouse Iapp locus [8]. Here, we report our findings that islets bearing the S20G gene mutation exhibit increased amyloid-induced beta cell apoptosis, decreased beta cell area and impaired insulin release.…”
Section: Introductionmentioning
confidence: 99%